Structural and chemical changes in cocoa (Theobroma cacao L) during fermentation, drying and roasting - de Brito, Edy S; García, Nelson H Pezoa; Gallão, M I; Cortelazzo, Angelo L; Fevereiro, Pedro S; Braga, Márcia R (Journal of the science of food and agriculture, 2001)
Cocoa seeds and pulp were fermented for 144 h, followed by natural drying. The tegument was removed and the cotyledons were broken into nibs which were roasted at 150 °C for 30 min. Non‐fermented material, material fermented for 24, 48 and 72 h, material fermented for 144 h and then dried, and also the roasted nibs, were all prepared for chemical and microscopic analyses. Light microscopy revealed the presence of anionic and cationic residues and of neutral sugars. During fermentation there was a reduction in the cytoplasmic content of phenolic compounds and in the number of protein bodies. The cell wall showed a reduction in anionic residues and a loss of crystallinity. These alterations were maximum after 72 h. Drying and roasting increased the number of damaged cells and reduced the amount of cytoplasmic material. The chemical analyses generally confirmed the microscopy results. The concentration of amino‐terminal groups and total free amino acids increased during fermentation (up to 72 h), but returned to the initial values after roasting. The principal chemical changes were related to reducing sugars, free amino acids, proteins and phenols, and PCA was suggested as a useful tool to compare different samples. Microscopic analysis revealed the degradation of protein and phenolic bodies and cellular damage during roasting. © 2000 Society of Chemical Industry